Official Samba-3 HOWTO and Reference Guide, The - Terpstra, John; Vernooij, Jelmer (Bruce Perens' Open Source series., 2003)
"The breadth of technical information provided in this book ensures that even the most demanding of administrators will find something they need." --Andrew Tridgell, President of the Samba Team and the original author of Samba The practical, authoritative, step-by-step guide to cutting IT costs with Samba-3! This is the definitive guide to using Samba-3 in production environments. It begins with the immense amount of HOWTO information published by the Samba Team and volunteers around the world . . . but that's just the beginning. The book's Samba Team editors have organized and edited this material around the practical needs of working Windows(R) administrators. UNIX(R)/Linux administrators will find all the answers they need as well. Whether you're deploying Samba for the first time, integrating Samba into a Windows 200x Active Directory environment, migrating from NT 4 or Samba 2.x, or using Samba in a UNIX/Linux environment, you'll find step-by-step solutions, carefully edited for accuracy, practicality, and clarity. You'll learn all you need to make intelligent deployment decisions, get running fast, and use Samba-3's powerful new features to maximize performance and minimize cost. Step-by-step installation techniques and proven configurations that work "right out of the box." Essential Samba-3 information that leverages your Windows networking knowledge Detailed coverage of Samba-3's powerful new user/machine account management, network browsing, and mapping capabilities Authoritative explanations of advanced features such as interdomain trusts and loadable VFS file system drivers Clear information on how Samba-3 handles Windows desktop/user policies and profiles Practical techniques for optimizing network printing Specific guidance for migration from Windows NT 4 or Samba 2.x Troubleshooting techniques that draw on the knowledge of the entire Samba community.